Characterization of Metabolite Landscape Distinguishes Medicinal Fungus Cordyceps sinensis and other Cordyceps by UHPLC-Q Exactive HF-X Untargeted Metabolomics - Chuyu Tang; Xiuzhang Li; Tao Wang; Jie Wang; Mengjun Xiao; Min He; Xiyun Chang; Yuejun Fan; Yuling Li (Molecules, 2023)
Cordyceps represent a valuable class of medicinal fungi with potential utilization. The overexploitation and resource scarcity of Cordyceps sinensis (CS) have led to the emergence of Cordyceps such as Cordyceps militaris (CM) and Cordyceps cicadae (CC) as substitutes. The medicinal value of CS is often considered superior to other Cordyceps, potentially owing to differences in active ingredients. This study aimed to evaluate the differences in the composition and abundance of the primary and secondary metabolites of CS and its substitutes by untargeted metabolomics. A total of 4671 metabolites from 18 superclasses were detected. CS and its substitutes were rich in amino acids, lipids, organic acids, and their derivatives. We statistically analyzed the metabolites and found a total of 285 differential metabolites (3′-Adenylic acid, O-Adipoylcarnitine, L-Dopachrome, etc.) between CS and CC, CS and CM, and CM and CC, which are potential biomarkers. L-glutamate and glycerophospholipids were differential metabolites. A KEGG enrichment analysis indicated that the tyrosine metabolic pathway and tryptophan metabolism pathway are the most differentially expressed pathways among the three Cordyceps. In contrast, CS was enriched in a higher abundance of most lipid metabolites when compared to CM and CC, which may be an indispensable foundation for the pharmacological functions of CS. In conclusion, systematic, untargeted metabolomics analyses for CS and other Cordyceps have delivered a precious resource for insights into metabolite landscapes and predicted potential components of disease therapeutics.